PEMBUATAN APLIKASI BERBASIS WEBSITE PADA KAMPUNG WAYANG - Eunike Eunike; Ery Dewayani; Wasino Wasino (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
Kampung Wayang located in the Kepuhsari village in Wonogiri, Central Java, be known as a center of Wayang Kulit craft. Crafts and wayang kulit culture in Kepuhsari has existed since more than half a century ago.But, to find more information and detail about kampung wayang is very difficult, the information that they got only a small part contained in Kampung Wayang, while some people want to know more detailed information about the craft or product as well as any activities offered by Kampung Wayang. Therefore, we need a media that can be used to provide more information and details about the Kampung Wayang well as to promote the crafts that have been generated by the residents of Kampung Wayang.So, purpose of making applications based website in Kampung Wayang is a media promotion Kampung wayang more effective and efficient as well as displaying and disseminating information about the art and culture in Kampung Wayang and the other activities offered by the existing people in Kepuhsari to be better known by the public.